Unexpected Consequences of Ricardian Expectations - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
Economists are widely familiar with the Ricardian equivalence thesis. It maintains that, given the time-path of government spending, a change in taxation does not alter the set of feasible life-time consumption plans of the households and affects neither the demand for commodities and services nor the rate of interest, provided the households act rationally. In this note a surprising finding is established. Assuming that the agents in a standard infinite horizon growth model hold the very expectations the thesis proposes (“Ricardian expectations”), it is shown that these expectations are invalidated. This divergence from the Ricardian equivalence thesis is traced to the omission of interest payments on public debt as part of the households' disposable income. The non-equivalence is valid in a wide class of models.
urn:nbn:de:bvb:19-epub-14847-8
Keywords: E2; E12; E6; H6; 330; Barro-Ricardo equivalence; Ricardian equivalence; fiscal policy; debt; taxation; rational expectations; Ricardian expectations; Barro expectations; tax neutrality; Ricardianische Äquivalenz; Erwartungstheorie; Rationale Erwartung; Theorie